MiR-136 inhibits gastric cancer–specific peritoneal metastasis by targeting HOXC10 - Jianyong Zheng; Peng Ge; Xiaonan Liu; Jiangpeng Wei; Guosheng Wu; Xiaohua Li (Tumor Biology, 2017)
Functions of microRNAs have been characterized in the embryologic, physiologic, and oncogenic processes, but the role of microRNAs in mediating tumor-specific organ metastasis was addressed only recently and still absent in gastric cancer peritoneal metastasis. Here, we used the microarray analysis to define the gastric cancer peritoneal metastasis–related microRNAs from highly peritoneal metastatic derivatives (GC-9811P cells) and the parental GC-9811 human gastric cancer cells. MiR-136 was found to be decreased in all peritoneal metastatic sublines when compared with that in the parental line. We further confirmed that miR-136 expression is frequently downregulated in gastric cancer peritoneal metastasis cells and tissues and its low expression is significantly associated with more peritoneal metastasis and worse prognosis. Moreover, restoring the expression of miR-136 could inhibit gastric cancer peritoneal metastasis in vitro and in vivo. Subsequent investigation characterized HOXC10 as a direct target of miR-136. In addition, knockdown of HOXC10 reduced GC-9811P cell migration and invasion, similar to the phenotype observed with miR-136 restoration in these cells, indicating that HOXC10 functions as a metastasis promoter in gastric cancer peritoneal metastasis. Upregulation of HOXC10 in parental GC-9811 cells resulted in a dramatic reduction of in vitro migration, invasion, and in vivo peritoneal metastasis. Furthermore, our results showed that ectopic expression of HOXC10 could reverse inhibition of metastasis by overexpressed miR-136 in GC-9811P cells. Our findings provide new insights into the role of miR-136 in the gastric cancer–specific peritoneal metastasis and implicate the potential application of miR-136 in gastric cancer peritoneal metastasis therapy.